Constitucionalismo sin consenso: una crítica a la Constitución de 1991 - Coral Lucero, James Iván (2023)
T hroughout its constitutional history, Colombia has tried to reach a consensus that supports a feasible political project. With the Constitution of 1991, Colombia opened a new process for public participation and more specifically a new democratic framework based on the legal recognition of fundamental rights for all Colombians. However, this consensus misses an important point: the formation of a civil society. This essay is an attempt to show how the elements for a consensus can be analyzed through John Rawls’s theory.